Renal impairment in intermittent chronic low dose organophosphate exposure: biochemical evidence - Aung, Sanda; Abdullah, Nor Zamzila; Talib, Norlelawati A.; Noor, Noriah Mohd; Mat Zainone, Zamzuria; Abdul Razak, Tariq (2015)

(untitled)
Organophosphates (OPs) pesticides are widely used in agriculture as pest control. Many people are exposed to chronic low dose of OPs through these activities. However, most of the studies on OPs mainly focused on its acute toxic effects rather than its chronic low dose effects. Limited epidemiology data and animal study found that there was evidence of nephrotoxicity in chronic low dose OPs exposure but the study lack of biochemical support. The aim of this study was to study the effect of chronic low dose OPs exposure on selected biochemical parameters of renal function in a rat model. 24 males Sprague-Dawley rats were randomly divided into 3 groups of 6 with Group 1 as a Control group. Group 2 and Group 3 received subcutaneous vehicle (3% dimethyl sulphoxide + 97% v/v soy oil) and 18.0 mg/kg BW chlorpyrifos (CPF) respectively every other day for 180 days. The intermittent dosing regimen is used to provide a model for the types of exposure that might be experienced by agricultural workers. Blood was analysed for urea, creatinine, glucose and advanced glycation end-products (AGEs). Urea and creatinine were significantly higher in OPs exposed group with significant correlation between urea and creatinine. OPs exposed group showed higher glucose and AGEs level than that of the control groups with significant correlation between glucose and AGEs. Significant correlations were also noted between both urea and creatinine with glucose but not with AGEs. Chronic intermittent low dose CPF exposure induces renal impairment with possible contribution from the effect of hyperglycaemia but not AGEs. Further study need to be done to explain the relevant mechanism.